Meteor head echo altitude distributions and the height cutoff effect studied with the EISCAT HPLA UHF and VHF radars - Westman, A.; Wannberg, G.; Pellinen-Wannberg, A. (HAL CCSD, 2004)
International audience Meteor head echo altitude distributions have been derived from data collected with the EISCAT VHF (224MHz) and UHF (930MHz) high-power, large-aperture (HPLA) radars. At the high-altitude end, the distributions cut off abruptly in a manner reminiscent of the trail echo height ceiling effect observed with classical meteor radars. The target dimensions are shown to be much smaller than both the VHF and the UHF probing wavelengths, but the cutoff heights for the two systems are still clearly different, the VHF cutoff being located several km above the UHF one. A single-collision meteor-atmosphere interaction model is used to demonstrate that meteors in the (1.3?7.2) µ g mass range will ionise such that critical electron density at 224MHz is first reached at or around the VHF cutoff altitude and critical density at 930MHz will be reached at the UHF cutoff altitude. The observed seasonal variation in the cutoff altitudes is shown to be a function of the seasonal variation of atmospheric density with altitude. Assuming that the electron density required for detection is in the order of the critical density, the abrupt altitude cutoffs can be explained as a consequence of the micrometeoroid joint size-speed distribution dropping off so fast at the large-mass, high-velocity end that above a certain altitude the number of detectable events becomes vanishingly small. Conversely, meteors at the low-mass end of the distribution will be gradually retarded such that the ionisation they generate never reaches critical density. These particles will remain unobservable.